Community justice as a conflict management mechanism in Thailand, Indonesia, the Philippines, and Myanmar - Glubwila, Sorat; Khruakham, Seksan; Boonpadung, Patinya (Kasetsart Journal of Social Sciences, 2021)
Community justice has recently been brought to the public attention in Thailand due to its promising outcomes in resolving problems embedded in the mainstream justice system. Apart from Thailand, community justice has been implemented in other ASEAN member countries including Indonesia, the Philippines, and Myanmar. This article examines what Thailand and the studied countries have accomplished with regards to community justice. This research employed qualitative methods to obtain data through in-depth interviews and focus group. In-depth interviews were carried out with eight experts in community justice in the four target countries, namely, Thailand, Indonesia, the Philippines, and Myanmar. Additionally, focus group was also held with 20 experts involved in conflict management and reconciliation from the countries under study. The results revealed various community justice practices within the four countries. In Thailand, mediation as a community justice process was practiced by the village committee, the district governor/administrative sector/Damrongtham Center, the Community Justice Center, and the Community Dispute Mediation Center. In Indonesia, community justice took the form of community policing, while in the Philippines, it was performed under the Katarungang Pambarangay (KP) or Barangay Justice System (BJS). In Myanmar, alternative dispute resolution was practiced by Community elders, Village leaders, 10/100HH leaders, or Ward/ Village Tract Administrator in Myanmar. This study provides suggestions to improve community justice in Thailand including making some part of community justice compulsory, promoting the role of community police and developing a training system for those involved in the conflict resolution process.